Improvement Productivity Menggunakan Metode Time Motion Study Pada Area Dissolving Soy PT XNX - Brivan Ardhandy Studynka; Enny Aryanny (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
PT XNX is a leading company operating in the food and beverage industry in Indonesia. This company produces based on demand, so the level of employee performance productivity is very important. There are many factors that influence worker productivity, such as experience, knowledge, and age. This research was conducted in the production department for 5 (five) months. The primary data collection method is by making direct observations in the field and using the time and motion study method, a systematic study of work systems with the aim of developing better systems and methods, standardizing systems and standards for determining time standards and selecting operators with a Lean Manufacturing approach, namely waste. or waste to increase labor productivity in the Production department area. The results were obtained in the form of recommendations for improvement, namely by optimizing productivity by means of operator efficiency from initially 6 people to 5 people, where before improvements were made, labor productivity was 53.11% in dissolving soy sauce, after improvements were made, labor productivity was 74.84. %. This has an effect on cost savings of IDR 4,515,133 for 26 working days, each day amounting to IDR 173,548. Therefore, there are 3 shifts in one day, so the total daily income is IDR 520,644 or a cost savings of 16.63%.